2011
DOI: 10.1177/1469787411402483
|View full text |Cite
|
Sign up to set email alerts
|

The relative benefits found for students with and without learning disabilities taking a first-year university preparation course

Abstract: Positive outcomes have been reported for university preparation courses for students without disabilities. Little is known about whether these courses can offer the same benefit to students with learning disabilities and whether the inclusion of psychosocial factors, in addition to academic skills, would benefit both groups. First-level students with and without learning disabilities were tested on variables known to influence academic performance at the beginning and end of a university preparation course. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Reed et al (2009) found that the course-intervention group had greater improvements in resourcefulness, academic self-efficacy, and grades compared to students in other intervention groups. In another study, Reed, Kennett, Lewis, and Lund-Lucas (2011) found that the benefits of interventions brought forward in an academic course for students with and without learning disabilities were the same; significant pre-to post-testing increases in academic resourcefulness and self-efficacy were observed for both groups of students. Extending this finding, the current study outcomes support that interventions incorporating modules on resourcefulness (coping with academic stress) may be particularly beneficial in learning to balance multiple roles.…”
Section: Discussionmentioning
confidence: 91%
“…Reed et al (2009) found that the course-intervention group had greater improvements in resourcefulness, academic self-efficacy, and grades compared to students in other intervention groups. In another study, Reed, Kennett, Lewis, and Lund-Lucas (2011) found that the benefits of interventions brought forward in an academic course for students with and without learning disabilities were the same; significant pre-to post-testing increases in academic resourcefulness and self-efficacy were observed for both groups of students. Extending this finding, the current study outcomes support that interventions incorporating modules on resourcefulness (coping with academic stress) may be particularly beneficial in learning to balance multiple roles.…”
Section: Discussionmentioning
confidence: 91%
“…Teaching & Learning Inquiry, 7(1). http://dx.doi.org/10.20343/teachlearninqu.7.1.9 150 resourcefulness strategies, with significant improvements observed in academic resourcefulness and grades for students completing the sessions, illustrating that these skills can be learned (Kennett, 1994;Reed et al, 2009;Reed, Kennett, Lewis, & Lund-Lucas, 2011. ) Moreover, engaging in greater academic self-regulation and attaining higher grades would hopefully allow students to recognize the importance of putting in the hours in the pursuit of academic success.…”
Section: Discussionmentioning
confidence: 99%
“…It is also conceivable that her resourcefulness skills were slowly evolving over time from the backing and advice of others that she described. Even though extant research provides evidence for the primary acquisition of resourcefulness skills in childhood and early adolescence (Leung & He, 2010;Zauszniewski, Chung, Chang, & Krafcik, 2002), other studies show that, with the proper social supports in place, resourcefulness skills can begin to evolve during late adolescence Reed, Kennett, Lewis, & Lund-Lucas, 2011) and even in late adulthood (Zauszniewski, 1997).…”
Section: Negative Case: S14mentioning
confidence: 99%
“…Hence, it would be beneficial for universities to help students to develop a sense of control over their studies. Fortunately, academic success and self-management training programs involving weekly seminars on topics ranging from problem solving and learning strategies to research skills to motivation have been effective at helping students learn resourceful and academic skills and modify their negative academic beliefs (Bowering, Mills, & Merritt, 2017;Kennett, 1994;Reed et al, 2011;Reed et al, 2009). Whereas resourceful behaviors are thought to be acquired in childhood and early adolescence through informal interactions with parents and significant others, particularly resourceful others adopting a warm, loving, and supportive parenting style (Rosenbaum, 1990;Turkel & Tezer, 2008;Zauszniewski et al, 2002), formal and extensive instruction of general and academic-specific resourceful behaviors by supportive and encouraging instructors who are knowledgeable in education techniques is important at the university level (Bowering et al, 2017).…”
Section: Conclusion and Future Researchmentioning
confidence: 99%